Effects of Global Geomagnetic Field Variations Over the Past 100,000 Years on Cosmogenic Radionuclide Production Rates in the Earth's Atmosphere - Panovska, Sanja; Poluianov, Stepan; Gao, Jiawei; Korte, Monika; Mishev, Alexander; Shprits, Yuri Y.; Usoskin, Ilya (Journal of Geophysical Research: Space Physics, 2023)
Abstract The production rates of cosmogenic radionuclides, such as 10 Be, 14 C, and 36 Cl, in the Earth's atmosphere vary with the geomagnetic field and solar activity. For the first time, the production rates of several cosmogenic nuclides are estimated for the past 100 ka based on global, time‐dependent geomagnetic field models and a moderate solar‐activity level. In particular, the production rates were high with no notable latitudinal dependence during the Laschamps geomagnetic excursion (41 ka BP). The mean global production of 10 Be over the Laschamps excursion was more than two times greater than the present‐day one, whereas the increase was 1.9 times for the Norwegian‐Greenland Sea excursion (∼65 ka), and only 1.3 times for the Mono Lake/Auckland excursion (∼34 ka). All analyzed geomagnetic field models covering the past 100 ka, including the modern and Holocene epochs, lead to hemispheric asymmetry in the production rates, persistent overall time ranges, and reflected in the time‐averaged nuclide production rates. Production rates predicted by the geomagnetic field models are in good agreement with actual measurements from ice cores and sediment records. These global, long‐term production rates are important for a wide range of studies that employ cosmogenic nuclides as a proxy/tracer of different Earth system processes. Key Points: We estimated the atmospheric production rates of cosmogenic radionuclides using global geomagnetic field models covering the past 100 ka The results show the importance of the multipolar components of the field during the Laschamps excursion The variations in production rates predicted by the models agree well with the actual measurements from ice cores Academy of Finland http://dx.doi.org/10.13039/501100002341 University of Oulu China Scholarship Council http://dx.doi.org/10.13039/501100004543 Helmholtz‐Zentrum Potsdam ‐ Deutsches GeoForschungsZentrum GFZ http://dx.doi.org/10.13039/501100010956 https://earthref.org/ERDA/2543/ https://earthref.org/ERDA/2498/ ...